Periodontal Management during COVID-19 Pandemic: Mini Review - Bayrakdar Sevda Kurt; Ilhan Betül; Bayrakdar Ibrahim Sevki; Alpay Funda Kurt; Orhan Kaan (Balkan Stomatological Society, 2021)
A few cases of pneumonia were reported by Wuhan Municipal Health Commission in Wuhan, Hubei Province, Republic of China and this mysterious pneumonia was recognized as novel coronavirus disease (COVID-19) in the course of time on 31 December 2019. Based on the literature knowledge, COVID-19 outbreak was came into existence through an animal-to-human transmission, then continued human-to-human diffusion. Especially dentists among the medical professionals are at high-risk group of SARS-CoV-2 virus contamination because of several routine dental procedures having the risk to convey the SARS-CoV-2 virus via droplets and close contact. In this mini review, it was aimed to give information about patient management during COVID-19 pandemic for dental practitioners, periodontologists and dental hygienists.